The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1365-2745.2011.01934.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf ageing promotes the shift in defence tactics in Mallotus japonicus from direct to indirect defence

Abstract: Summary1. Most plant species rely upon multiple lines of defence that develop or change functions with leaf age. To date, the effects of leaf age on multiple defence traits have been insufficiently elucidated. For Mallotus japonicus (Euphorbiaceae), we report a shift from direct to indirect defence against herbivory. That shift occurs gradually during leaf ageing. 2. First, the densities of trichomes and pellucid dots, the numbers of extrafloral nectaries (EFNs) and pearl bodies, and the number of ants on leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(77 citation statements)
references
References 48 publications
(69 reference statements)
0
77
0
Order By: Relevance
“…A plausible answer for the use of direct defence traits is that physical and chemical resistance traits function complementarily: chemical resistance is effective for various herbivores, except for some specialist herbivores that have adapted to toxic chemicals synthesized by their host plants (Howe & Westley 1988;van der Meijden 1996;Gatehouse 2002); physical resistance defends the leaves from both generalist and specialist herbivores (Agrawal 2004;Handley, Ekbom & Agren 2005). For the use of biotic defence, Yamawo et al (2012b) pointed out that the effectiveness of biotic resistance by ants was unstable because ant abundance in the habitat affected the defence efficiency. Therefore, plants that use biotic resistance undergo strong herbivory in some habitats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A plausible answer for the use of direct defence traits is that physical and chemical resistance traits function complementarily: chemical resistance is effective for various herbivores, except for some specialist herbivores that have adapted to toxic chemicals synthesized by their host plants (Howe & Westley 1988;van der Meijden 1996;Gatehouse 2002); physical resistance defends the leaves from both generalist and specialist herbivores (Agrawal 2004;Handley, Ekbom & Agren 2005). For the use of biotic defence, Yamawo et al (2012b) pointed out that the effectiveness of biotic resistance by ants was unstable because ant abundance in the habitat affected the defence efficiency. Therefore, plants that use biotic resistance undergo strong herbivory in some habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Trichomes, which are produced on leaf surfaces, serve as a physical resistance trait (Yamawo et al 2012a,b). Pellucid dots, which also are present on leaf surfaces, typically contain toxic metabolic substances or essential oils (Wittstock & Gershenzon 2002;Schilmiller, Last & Pichersky 2008;Sirikantaramas, Yamazaki & Saito 2008) and function as a chemical resistance trait (Yamawo et al 2012b). Furthermore, the plant bears extrafloral nectaries (EFNs) on its leaf edges and food bodies (pearl bodies) on its leaf and stem surfaces as biotic resistance traits (Yamawo et al 2012a,b).…”
Section: S T U D Y S P E C I E Smentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in some cases, the presence of ants may even be undesirable, as they may frighten some possible disperses (Madden & Young 1992;Stapley 1998;Thomas 1988). A recent study performed by Yamawo et al (2012b) showed that the plants can gradually shift from direct to indirect defense against herbivory during leaf aging. Here, we show that the likely change in defense tactics during the ontogenic stages of the fruits of A. verrucosa supports the 'optimal defense theory' (McKey 1974(McKey , 1979Rhoades 1979), in which, plant tissues most closely linked to fitness, such as fruits, should be most defended at high and different levels.…”
Section: Discussionmentioning
confidence: 99%